Oral manifestations in patients affected by COVID-19 and their levels of treatment in environments with dental support: an integrative literature review (Research, Society and Development, 2022)
Introduction: The new coronavirus disease or COVID-19 causes an infection that can affect the respiratory system and trigger disorders in vital organs of the human body, in addition to having a high rate of transmissibility and causing several comorbidities. Among its main symptoms, the following stand out: fever, cough, headache, diarrhea, fatigue and myalgia. The diagnosis of this pathology may be associated with oral manifestations such as edema. Objectives: To compile the possible oral manifestations in patients with COVID-19. Methodology: This is an integrative literature review. To collect information, searches were made in PubMed, Scientific Electronic Library Online and Virtual Health Library databases by consulting the descriptors: “COVID-19”, “Oral Manifestations” and “Dental Care”. Full articles in English, Portuguese and/or Spanish published between 2015 and 2022 were selected. Results: 29 studies were selected whose analysis allowed to identify that the appearance of oral manifestations in patients with a positive diagnosis for COVID-19 can be promising. To detect the progression of the new coronavirus, there is an association of its signs and symptoms such as dysgeusia, hypogeusia, anosmia and hyposalivation, concomitantly associated with the appearance of oral pathologies such as aphthous lesions, ulcers and  periodontitis. Conclusions: Although the literature does not have definitive conclusions about the direct relationship between COVID-19 and oral manifestations, it has been evidenced in almost its entirety in the analyzed studies. Therefore, it is important to emphasize the role of the dental surgeon in the early detection and treatment of pathological manifestations that may be related to SARS-CoV-2, thus reducing the morbidity and mortality of cases.